2020
DOI: 10.1101/2020.11.06.372037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Landscape analysis of escape variants identifies SARS-CoV-2 spike mutations that attenuate monoclonal and serum antibody neutralization

Abstract: Although neutralizing antibodies against the SARS-CoV-2 spike (S) protein are a goal of most COVID-19 vaccines and being developed as therapeutics, escape mutations could compromise such countermeasures. To define the immune-mediated mutational landscape in S protein, we used a VSV-eGFP-SARS-CoV-2-S chimeric virus and 19 neutralizing monoclonal antibodies (mAbs) against the receptor binding domain (RBD) to generate 48 escape mutants. These variants were mapped onto the RBD structure and evaluated for cross-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
208
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(216 citation statements)
references
References 44 publications
7
208
0
1
Order By: Relevance
“…Y453F and N439K both also increase affinity for ACE2 (Starr et al, 2020b;Thomson et al, 2020) , and both escape some monoclonal antibodies (Baum et al, 2020;Starr et al, 2020a;Thomson et al, 2020) but neither greatly impact serum antibody binding by the samples we tested. Finally, S477N also reduces neutralization by some monoclonal antibodies (Liu et al, 2020b) , but did not greatly affect binding by the samples we tested.…”
Section: Rbd Mutations That Reduce Serum Binding and Neutralization Imentioning
confidence: 74%
See 1 more Smart Citation
“…Y453F and N439K both also increase affinity for ACE2 (Starr et al, 2020b;Thomson et al, 2020) , and both escape some monoclonal antibodies (Baum et al, 2020;Starr et al, 2020a;Thomson et al, 2020) but neither greatly impact serum antibody binding by the samples we tested. Finally, S477N also reduces neutralization by some monoclonal antibodies (Liu et al, 2020b) , but did not greatly affect binding by the samples we tested.…”
Section: Rbd Mutations That Reduce Serum Binding and Neutralization Imentioning
confidence: 74%
“…A multitude of recent studies have identified viral mutations that escape monoclonal antibodies targeting the SARS-CoV-2 spike (Baum et al, 2020;Greaney et al, 2020;Li et al, 2020;Liu et al, 2020b;Starr et al, 2020a;Weisblum et al, 2020) . However, it remains unclear how mutations that escape specific monoclonal antibodies will affect the polyclonal antibody response elicited by infection or vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate potential viral escape from neutralization mediated by the potent neutralizing NTD mAbs, we passaged a replication competent VSV-SARS-CoV-2 chimera in which the native glycoprotein was replaced by the SARS-CoV-2 S Wuhan-1 gene in the presence of S2L28, S2M28, S2×28 and S2×333, as previously described (Case et al, 2020; Liu et al, 2020b). Selective pressure provided by each mAb led to emergence of several escape mutants that clustered within the antigenic supersite i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the supposed mechanism leading to reinfection is a loss of protection elicited after the first episode, as it is known for other human coronaviruses [ 9 ]. The only mutation found in the spike region between the two episodes has not been associated with reduced neutralization by human convalescent sera [ 10 ]. In vitro, this mutation may lead to monoclonal antibodies neutralization resistance but whether this is relevant for human reinfections remains to be studied.…”
Section: Discussionmentioning
confidence: 99%